POROSITAS DAN PERMEABILITAS BETON ABU SEKAM PADI SEBAGAI BAHAN PERKERASAN KAKU (RIGID PAVEMENT) - Uu Saepudin (Sekolah Tinggi Teknologi Mandala Bandung, 2013)
Observations in the field that has the potential of rice husk ash is used as a mixture ofconcrete, this is due to reduce environmental pollution also can improve the quality of theproduct. But until now the use of rice husk ash as an added ingredient in the mix that canimprove the permeability and porosity of the concrete still needs to be analyzed. Thepurpose of this study was to determine the effect of the addition of rice husk ash inconcrete mix to the porosity and permeability of the concrete, and to investigate theaddition of rice husk ash optimum porosity and permeability of concrete to a minimum.The method used in this study is an experimental method.Based on the test results, the role of rice husk ash as filler space, adding impermeableconcrete, all variations of the addition of rice husk ash produced less concrete porosityvalues. The smaller the value of concrete permeability so that the concrete morewaterproof. The addition of rice husk ash optimum occurs in the addition of 30% byproducing porosity and permeability values of 10.93% and a minimum of 2.098 x 10-7 m /sec.